Teori Permintaan dalam Perspektif Ekonomi Islam: Prinsip, Faktor, dan Komparasi dengan Ekonomi Konvensional - Qurrotul Uyun; Ichsan Iqbal (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Demand theory occupies a central position in economic analysis because it explains consumer behavior in allocating limited resources. Within Islamic economics, demand is not solely determined by price and purchasing power but is also guided by moral, ethical, and sharia principles that shape consumption decisions. Despite the growing discussion of Islamic demand theory, previous studies have generally examined its principles, determinants, or comparisons with conventional economics separately, leaving limited integrative analyses that combine these dimensions into a comprehensive framework. Employing a qualitative library research approach, this article synthesizes classical Islamic economic literature, contemporary scholarly works, and relevant scientific publications through descriptive and comparative content analysis. The analysis demonstrates that Islamic demand theory differs fundamentally from conventional demand theory in its normative foundation, consumption objectives, and decision-making framework. Consumer demand is restricted by halal and haram principles, directed toward achieving maslahah and falah, and structured according to the hierarchy of maqashid al-shariah. Although both perspectives recognize price, income, substitute goods, and consumer preferences as determinants of demand, Islamic economics incorporates additional moral, spiritual, and social responsibility dimensions that influence consumption behavior. These findings provide a more comprehensive conceptual framework for understanding Islamic demand theory while strengthening the theoretical discourse of Islamic microeconomics and offering practical implications for consumer education, halal industry development, and Islamic economic policymaking.